Physicochemical and conductivity studies of chitosan-tapioca flour-LiBF4 gel polymer electrolytes - Siti Shafiqah Azahar (Elsevier, 2021)
The present study emphasizes the isolation of chitin and chitosan from the exoskeleton of white shrimp, Fenneropenaeus indicus. Demineralization and deproteination were used to extract chitin, followed by deacetylation of the extracted chitin to yield chitosan. Chitin and chitosan were characterized by FT-IR, TGA, SEM, XRD and CP-MAS 13C NMR analyses. FT-IR spectra presented characteristic peaks at 1655 cm−1 (amide) and 3441 cm−1 (hydroxyl). XRD analysis outlined two peaks at 9.41⁰ and 19.29⁰. Different compositions of CS-TF-LiBF4 gel polymer electrolytes were fabricated successfully using chitosan (CS), tapioca flour (TF), and lithium tetrafluoroborate (LiBF4) as organic filler, polymer host, and primary ions carrier to the polymer matrix, respectively. Gel polymer electrolytes were investigated through electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) to infer their ionic conductivity. It was revealed that electrical conductivity improved with increasing LiBF4 concentration from 0% to 10%. The maximum ionic conductivity was found to be 2.699 ± 0.28 mS cm−1 for CS-TF-10% LiBF4 biopolymer electrolyte with an electrochemical stability window potential of 2.34 V. EIS analysis showed that LiBF4 facilitated to enhance the amount of charge carried along with providing free ions for conduction.